2013
DOI: 10.1016/j.atherosclerosis.2013.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia enhances lipid uptake in macrophages: Role of the scavenger receptors Lox1, SRA, and CD36

Abstract: Hypoxia increases lipid uptake into macrophages and differentially regulates the expression of oxLDL receptors. Lox-1 plays a major role in hypoxia-induced foam cell formation which is, at least in part, mediated by HIF-1α.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 41 publications
6
82
0
1
Order By: Relevance
“…Additionally, the elevated rate of cardiovascular comorbidities (3 or more) in the frail group, suggests that they are more likely to have arterial diseases with inflammation, coagulation disorders and lower rates of peripheral oxygenation (Crucet et al, 2013;Parathath et al, 2011). The high frequency of HF in our sample (80%) may corroborate these findings.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, the elevated rate of cardiovascular comorbidities (3 or more) in the frail group, suggests that they are more likely to have arterial diseases with inflammation, coagulation disorders and lower rates of peripheral oxygenation (Crucet et al, 2013;Parathath et al, 2011). The high frequency of HF in our sample (80%) may corroborate these findings.…”
Section: Discussionsupporting
confidence: 76%
“…Hypoxia has been implicated as a pathogenic factor in atherosclerosis and contributes to the proatherosclerotic functions of macrophages ( Figure 2A) (117). Several reports showed that lipid uptake and foam cell formation are dependent on hypoxia and HIF-1α (118)(119)(120). Both murine and human macrophage cell lines increase cellular neutral lipid content when cultured under hypoxic conditions; however, this effect is reversed upon HIF-1α depletion.…”
Section: Hifs In Myeloid Cellsmentioning
confidence: 99%
“…Obviously, foam cell formation is a key event in both early and late atherosclerotic lesions. It has been demonstrated that scavenger receptors A (SRA, also known as macrophage scavenger receptor 1, MSR1), lectin-like ox-LDL receptor (LOX-1), and cluster of differentiation 36 (CD36) are the most relevant for cholesterol uptake [25]. On the other hand, to prevent the accumulation of excess cholesterol, the esterification of cholesterol is mediated by the microsomal enzyme acyl-coenzyme A: cholesterol acyltransferase (ACAT) [26] and the efflux of cholesterol or reverse cholesterol transport is regulated by the transporters ATP binding cassette transporter A1 (ABCA1), ATP binding cassette transporter G1 (ABCG1) [27,28].…”
Section: Accepted Manuscriptmentioning
confidence: 99%